Perlindungan Terhadap Kombatan Yang Berstatus Tawanan Perang Dalam Situasi Konflik Bersenjata Menurut Hukum Humaniter Internasional (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to examine the legal protection provided by international humanitarian law to combatants who become prisoners of war during armed conflict, as well as to identify the legal mechanisms applied to address violations of this protection. The methods used in this study include a legal approach, case analysis, and conceptual review. The findings of this study reveal that international humanitarian law, particularly the 1949 Geneva Conventions, provides comprehensive protection for prisoners of war, including basic rights such as humane treatment, health, and welfare, as well as preventing torture or cruel treatment. The Conventions ensure that the rights of combatants are respected without discrimination, even when they are under enemy control. Enforcement mechanisms involve the obligation of states to adopt national laws in accordance with the Convention and to prosecute serious violations through national courts, with the support of international mechanisms such as ad hoc tribunals and the International Criminal Court (ICC) if necessary.